Enantioenriched α-substituted glutamates/pyroglutamates via enantioselective cyclopropenimine-catalyzed Michael addition of amino ester imines - Zara M. Seibel; Jeffrey S. Bandar; Tristan H. Lambert (Beilstein Journal of Organic Chemistry, 2021)
A procedure for the enantioselective synthesis of α-substituted glutamates and pyroglutamates via a cyclopropenimine-catalyzed Michael addition of amino ester imines is described. Enantioselectivities of up to 94% have been achieved, and a variety of functional groups were found to be compatible. The impact of the catalyst structure and imine substitution is discussed. Compared to other methods, this protocol allows for a broader and more enantioselective access to pyroglutamate derivatives.